DRYMONIA SQUAMOSA (GESNERIACEAE), A NEW SPECIES FROM LAS ORQUÍDEAS NATIONAL NATURAL PARK (ANTIOQUIA, COLOMBIA) (2015)
A new species of Drymonia (Gesneriaceae) from the Cordillera Occidental of the Colombian Andes in the department of Antioquia is described and illustrated. The new species, Drymonia squamosa, is distinguished by dense clusters of scales on the petioles, glabrate leaf blades with minute punctations on the lower surface, calyx appearing swollen at base with lanceolate lobes, corolla villous to lanate, and style with glandular trichomes. Additionally, D. squamosa is categorized as vulnerable (VU) based on the IUCN criteria.